Low Temperature Phase Diagrams for Quantum Perturbations of Classical Spin Systems - Borgs, Christian; Kotecky, Ricardo; Ueltschi, D. (Commun. Math. Phys., 1996)
We consider a quantum spin system with Hamiltonian.